2014
DOI: 10.1007/s10098-014-0773-0
|View full text |Cite
|
Sign up to set email alerts
|

Spent coffee grounds for biodiesel production and other applications

Abstract: This work evaluates the possibility of using spent coffee grounds (SCG) for biodiesel production and other applications. An experimental study was conducted with different solvents showing that lipid content up to 6 wt% can be obtained from SCG. Results also show that besides biodiesel production, SCG can be used as fertilizer as it is rich in nitrogen, and as solid fuel with higher heating value (HHV) equivalent to some agriculture and wood residues. The extracted lipids were characterized for their propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(64 citation statements)
references
References 17 publications
3
43
2
5
Order By: Relevance
“…5, 5 and 10% (v/v This causes not only the loss of organic matter, but also the time and effort necessary to carry out the composting process. Spent coffee grounds (SCG) material includes a wide range of valuable organic compounds which contain, among others, tannic acid, cellulose, hemicellulose, lipids, organic acids and polyphenols and therefore it is used for the production of biochar, for composting as a sorbent and for the preparation of biodiesel [2][3][4]. SCG has been also considered as valuable source of polyphenols and galactomannans for application in medicine, cosmetics and food industry [5].…”
mentioning
confidence: 99%
“…5, 5 and 10% (v/v This causes not only the loss of organic matter, but also the time and effort necessary to carry out the composting process. Spent coffee grounds (SCG) material includes a wide range of valuable organic compounds which contain, among others, tannic acid, cellulose, hemicellulose, lipids, organic acids and polyphenols and therefore it is used for the production of biochar, for composting as a sorbent and for the preparation of biodiesel [2][3][4]. SCG has been also considered as valuable source of polyphenols and galactomannans for application in medicine, cosmetics and food industry [5].…”
mentioning
confidence: 99%
“…The bound moisture content depends on the physical nature of the solid, drying temperature and time and it can be a limiting factor to the drying rate (9). Following haracteristics of SCG can be determined: content of moisture, total carbon, total nitrogen, protein, ash, cellulose, and insoluble (or Klason) and soluble lignin content (17).…”
Section: Oil Extraction From Spent Coffee Groundsmentioning
confidence: 99%
“…The solvent is then recovered in order to be used in the next batch of extraction (9). The oil quality is then assessed by determining the iodine number, the saponification, calorific values, acid value (AV), and content of water, kinematic viscosity, viscosity index, density and elemental composition (9,17). Moreover, the heating value of the SCG after extraction is measured.…”
Section: Oil Extraction From Spent Coffee Groundsmentioning
confidence: 99%
“…Approximately 8 million tonnes of coffee grounds are produced each year [9], which represents a relatively pure waste stream that could be used for biofuel production. A number of studies have demonstrated the suitability of coffee biodiesel as a potential fuel feedstock [10][11][12][13][14]. Interestingly while these studies used coffee from various local areas, the fatty acid profile was relatively constant consisting of four major fatty acids; palmitic acid (C16:0, ~35%), stearic acid (C18:0, ~8%), oleic acid (C18:1, ~5%) and linoleic acid (C18:2, ~44%).…”
Section: Introductionmentioning
confidence: 99%